Mitigating Visually Induced Motion Sickness: A virtual hand- eye coordination task. (September 2015) - Curtis, Michael K; Dawson, Kayla; Jackson, Kelli; Litwin, Liat; Meusel, Chase; Dorneich, Michael C.; Gilbert, Stephen B.; Kelly, Jonathan; Stone, Richard; Winer, Eliot
Virtual reality has grown rapidly over the past decade, yet visually induced motion sickness (VIMS), continues to affect the usability of this technology. Aside from medicine, physical hand-eye-coordination tasks have been found to be effective in mitigating symptoms of VIMS, however the need for equipment outside of virtual reality limits the usefulness of these mitigation techniques. In this study, 21 participants were sickened via a virtual obstacle course and used one of two mitigation techniques. The first, natural decay, is simply waiting outside the virtual environment (VE) for symptoms to subside; the other was a virtual peg-in-hole task, performed in the VE with a gamepad. A paired samples t-test confirmed that the virtual obstacle course induced VIMS. Both mitigation techniques significantly lessened the symptoms of VIMS, but there were no significant differences in the effectiveness of mitigation between the two techniques. A virtual mitigation method allowing continued immersion in a VE would pave the way for long-term immersion virtual reality studies, involving topics such as vigilance or training.